ANALISIS SISTEM INFORMASI AKUNTANSI PENGELUARAN DAN PENERIMAAN KAS PADA PT. UNILEVER - Rahmawati, Nita; Helmita, Helmita; Oktaria, Eka Travilta; Ananda, Shinta Merinda (Business and Enterpreneurship Journal (BEJ), 2024)
PT Unilever Indonesia is one of the leading companies in Indonesia operating in the consumer goods industry, and has led this industry for 86 years. The purpose of this research is to determine the analysis of the accounting information system for cash expenditures and receipts that has been implemented at PT. Unilever. This type of research uses a qualitative approach. A qualitative approach is a research approach that produces findings without using statistical procedures or other forms of calculation. Through this qualitative approach, the research results obtained are adjusting the applicable rules and procedures by making in-depth observations and not generalizations. An accounting information system is one of the important things that must be in place in managing the implementation of good government. If a company does not have a structured and coherent accounting information system, the entity will easily experience fraud or misappropriation for personal gain. Keywords: accounting information system